MultiColor imaging in the evaluation of geographic atrophy due to age-related macular degeneration. Issue 6 (13th January 2015) - Moussa, Naima Ben; Georges, Anouk; Capuano, Vittorio; Merle, Benedicte; Souied, Eric H; Querques, Giuseppe
Abstract : Purpose: To compare different imaging modalities and to investigate the ability of MultiColor to evaluate geographic atrophy (GA) due to age-related macular degeneration (AMD). Methods: Twenty-two consecutive patients with GA underwent MultiColor, colour fundus photography, blue fundus autofluorescence (FAF) (excitation=488 nm; emission >500 nm), near-infrared FAF (NIR-FAF) (excitation=787 nm; emission >800 nm) and spectral-domain optical coherence tomography (SD-OCT) (Spectralis HRA+OCT; Heidelberg Engineering) imaging. Two readers independently measured the size (area) and the width of GA (on horizontal SD-OCT scan cutting the fovea), and evaluated the foveal sparing in each examination. Results: A total of 32 eyes (22 patients, mean age 79.2±8 years) with GA were included. Intragrader and intergrader agreement considering the evaluation of the size and width of GA was high for all the examinations. MultiColor and FAF showed the greatest intergrader agreement for GA area measurement (intraclass correlation (ICC)=0.990, 95% CI 0.980 to 0.995; ICC=0.998, 95% CI 0.996 to 0.999, respectively). SD-OCT showed the highest intergrader agreement of foveal involvement (k=1), followed by MultiColor and NIR-FAF (k=0.68). Conclusions: We demonstrated that several different imaging modalities currently available in clinical practice are reliable for evaluating GA due to AMD. MultiColor is an excellent tool for the measurement of GA area and width, and for the detection of foveal sparing.